1982
DOI: 10.1007/bf00283749
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal profiles of plasma magnesium and blood glucose in diabetes

Abstract: Summary. In order to study the relation between plasma magnesium and blood glucose concentrations in diabetes, diurnal profiles were obtained in nine diabetic patients and five healthy subjects. A significant inverse relationship between the two variables was found in seven of the nine diabetic patients and in one healthy subject. This could not be attributed solely to changes in plasma albumin, and its mechanism is unclear. Plasma magnesium levels in diabetes are closely dependent on blood glucose concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 9 publications
2
9
0
1
Order By: Relevance
“…(4). A few case of diabetes were given magnesium sulfate intravenously for several months showed decrease of blood glucose and HbA1~ (unpublished observations).…”
Section: Methods and Subjectsmentioning
confidence: 94%
“…(4). A few case of diabetes were given magnesium sulfate intravenously for several months showed decrease of blood glucose and HbA1~ (unpublished observations).…”
Section: Methods and Subjectsmentioning
confidence: 94%
“…Peroxidation of lipoproteins due to free radical production and increased platelet aggregation may also contribute to the development of atherosclerosis. Seelig and Hegetveit [89] and Mathur [90] have suggested that magnesium can prevent atherosclerotic disease by counteracting the adverse effect of excessive intracellular calcium, retaining intracellular potassium and contributing both to stabilize the plasma membrane and maintaining the integrity of subcellular structures. VanRoelen et al [91] also confirmed the negative correlation between poor erythrocyte magnesium content and severity of the microangiopathy.…”
Section: Magnesium and Cardiovascular Diseasesmentioning
confidence: 99%
“…Experimental magnesium de fi ciency is characterized by increased triglycerides, cholesterol, VLDL, LDL, apolipoprotein B and triglyceride-rich lipoproteins A1, and plasma lecithin-cholesterol acyltransferase activity [ 69 ] . Magnesium can prevent atherosclerotic disease by counteracting the adverse effect of excessive intracellular calcium, retaining intracellular potassium, and contributing both to stabilize the plasma membrane and to maintain the integrity of subcellular structures [ 70,71 ] . Magnesium supplementation of hyperlipidemic subjects has been shown to cause a reduction in total and LDL cholesterol and apolipoprotein B and an increase in HDL cholesterol and triglycerides [ 67 ] .…”
Section: Magnesium De Fi Ciency and Type 2 Diabetesmentioning
confidence: 99%